Detection of BCR/ABL gene in chronic Myeloid Leukaemia: comparison of Fluorescence in situ Hybridisation (FISH), conventional Cytogenetics and Polymerase Chain Reaction (PCR) techniques - Reena RMZ,; Julia Munchar MJ,; Salwati S,,; Hamidah NH,; Zubaidah Z,; Sharifah NA,; Cheong SK, (Penerbit UKM, 2006)
The reciprocal translocation t(9;22)(q34;q11) which gives rise to the Philadelphia (Ph1) chromosome and BCR/ABL fusion gene, plays a pivotal role in the diagnosis and pathogenesis of chronic myeloid leukemia (CML). In this study, we evaluated the role of fluorescence in situ hybridisation (FISH) in detecting the BCR/ABL rearrangement in CML patients. The sensitivity, specificity and detection rate of BCR/ABL gene using FISH, PCR and conventional cytogenetics (karyotyping) methods were also compared. 18 bone marrow samples of patients with clinically diagnosed CML and suspected of CML were collected. The sensitivity, specificity and positive predictive values of FISH were altogether